Unsintered sliding bearing blank and method for preparing sliding bearing blank

By using a vibrator to layer copper powder and copper-tin nickel alloy powder in the unsintered blank of sliding bearings, a dense copper layer and copper-tin nickel alloy layer is solved, and the product quality is improved The service life is achieved and efficient assembly line production is achieved.

CN114309617BActive Publication Date: 2025-01-10ZHEJIANG CHANGSHENG SLIDING BEARINGS
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202111675089.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-31
Publication Date
2025-01-10
Estimated Expiration
2041-12-31

AI Technical Summary

Technical Problem

During the manufacturing process, existing sliding bearings are prone to cracking or falling off due to the poor bonding strength between the copper-tin-nickel alloy layer and the substrate, resulting in product quality problems, especially inadequate performance under high loads and complex working conditions.

Method used

A sliding bearing unsintered blank is adopted, including a layer of substrate, a layer of laid copper powder layer and a layer of copper tin nickel alloy powder layer. The copper powder and copper tin nickel alloy powder are divided by a vibration machine at a frequency of 20 to 50Hz. The layer is formed, a dense copper layer of non-spherical copper powder and a spherical copper-tin-nickel alloy layer, which improves bonding strength and controls temperature and time during the sintering process to ensure the integrity of the copper layer.

Benefits of technology

It significantly improves the bonding strength and product quality of sliding bearings, can be used stably under high loads and complex working conditions, extends service life, and realizes efficient batch production of assembly line production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114309617B_ABST
    Figure CN114309617B_ABST
Patent Text Reader

Abstract

An unsintered blank of a sliding bearing and a method for preparing the same, wherein the unsintered blank of the sliding bearing comprises a substrate, a copper powder layer laid on the substrate, and a copper-tin-nickel alloy powder layer on the copper powder layer. The content of the copper powder in the mixture of the copper powder used to form the copper powder layer and the copper-tin-nickel alloy powder used to form the copper-tin-nickel alloy powder layer is 5-20%, the content of the micro-wax powder is 0.1-0.5%, and the rest is copper-tin-nickel alloy powder. The particle size of the copper-tin-nickel alloy powder is 0.05 mm to 0.10 mm. The particle size of the copper powder is 0.013 mm to 0.045 mm. The particle size of the micro-wax powder is less than 0.02 mm, and the micro-wax powder is sandwiched between the copper powder and the copper-tin-nickel alloy powder. The sliding bearing blank can improve the bonding strength between the sliding bearing blank and the substrate as well as the bonding strength inside the entire sliding bearing blank. In the subsequent preparation process of the sliding bearing, whether it is turning or milling, bending or stretching, it will not crack or shift, thereby improving the product quality and service life of the sliding bearing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sliding bearing manufacturing, in particular to an unsintered sliding bearing blank and a preparation method of the sliding bearing blank. Background Art

[0002] Wear-resistant composite materials used in sliding bearings are specially modified and widely used in the field of friction materials with their excellent anti-friction and wear-resistant properties. They also have excellent properties such as shock absorption, low noise, light weight, and easy processing. With the widespread application of wear-resistant composite materials, customer design requirements and working conditions are becoming higher and higher, especially when the load-bearing capacity requirements are higher, and the performance requirements for sliding bearings are also higher.

[0003] At present, for sliding bearings used in the fields of automotive steering gear bearings, seat recliner bushings, etc., which are used for reciprocating, rotating, and swinging motions under grease lubrication, high load, and low speed, a copper-tin-nickel alloy layer is usually sintered on the substrate. However, in actual applications, due to the poor bonding strength between the copper-tin-nickel alloy layer and the substrate, especially when the substrate is made of medium-carbon steel, high-carbon steel, or stainless steel, which has poor sintering composite properties, it is particularly easy to crack during the processing. For example, when preparing circular or other shaped sliding bearings, it is inevitable to perform processes such as turning, milling, bending, and drawing on them. During the manufacturing process of existing sliding bearings, due to the poor bonding strength, the copper-tin-nickel alloy layer itself often cracks, or even falls off from the substrate, causing product quality problems. Summary of the invention

[0004] In view of this, it is necessary to provide a sliding bearing blank with good bonding strength to prepare a sliding bearing to solve the above problems.

[0005] A sliding bearing unsintered blank, comprising a substrate, a copper powder layer laid on the substrate, and a copper-tin-nickel alloy powder layer on the copper powder layer. The content of the copper powder in the mixture of the copper powder used to form the copper powder layer and the copper-tin-nickel alloy powder used to form the copper-tin-nickel alloy powder layer is 5-20%, the content of the micro-wax powder is 0.1-0.5%, and the rest is copper-tin-nickel alloy powder. The particle size of the copper-tin-nickel alloy powder is 0.05mm-0.10mm and its shape is round spherical or elliptical. The particle size of the copper powder is 0.013mm-0.045mm and its shape is non-spherical. The particle size of the micro-wax powder is less than 0.02mm, and the micro-wax powder is sandwiched between the copper powder and the copper-tin-nickel alloy powder.

[0006] Furthermore, the substrate is medium carbon steel, high carbon steel, aluminum plate, steel plate or stainless steel plate.

[0007] Furthermore, the content of the copper powder is 13%, and the particle size of the copper powder is 0.017 mm.

[0008] Furthermore, the content of the copper powder is 10%, and the particle size of the copper powder is 0.025 mm.

[0009] Furthermore, the copper powder has a particle size of 0.015 mm to 0.035 mm, and the content of the copper powder in the mixture is 6-15%.

[0010] Furthermore, the copper-tin-nickel alloy powder is CuSn8Ni1.

[0011] Furthermore, the copper powder is pure copper powder or copper alloy powder, and the copper alloy powder is one of brass, red copper, bronze, and nickel silver.

[0012] A method for preparing a sliding bearing blank comprises the following steps:

[0013] S1: providing a mixture of copper-tin-nickel alloy powder, copper powder, and micro-wax powder, wherein the content of the copper powder in the mixture is 5-20%, the content of the micro-wax powder is 0.1-0.5%, and the rest is copper-tin-nickel alloy powder, the particle size of the copper-tin-nickel alloy powder is 0.05mm-0.10mm and the shape is round spherical or elliptical spherical, the particle size of the copper powder is 0.013mm-0.045mm and the shape is non-spherical, and the particle size of the micro-wax powder is less than 0.02mm;

[0014] S2: providing a substrate;

[0015] S3: stirring the mixture of the copper-tin-nickel alloy powder, copper powder and micro wax powder evenly and spreading the mixture on the surface of the substrate;

[0016] S4: providing a vibration machine, and placing a substrate covered with the mixture of the copper-tin-nickel alloy powder, copper powder, and micro wax powder on the vibration machine;

[0017] S5: starting the vibration machine and controlling the frequency of the vibration machine to be 20-50 Hz, the vibration time is 30 seconds when the thickness of the mixture is less than or equal to 0.5 mm, the vibration time is 100 seconds when the layer thickness of the mixture is greater than 0.5 mm and less than or equal to 2.0 mm, and the vibration time is 150 seconds when the copper powder layer thickness is greater than 2.0 mm to separate the copper powder and the copper-tin-nickel alloy powder into layers;

[0018] S6: Sintering the substrate on which the layered copper powder and copper-tin-nickel alloy powder are laid and rolling to prepare the sliding bearing blank.

[0019] Furthermore, in step S6, during the initial firing, when the sintering temperature reaches 200 degrees, the heating rate is controlled, and the temperature is slowly raised to 500 degrees at a rate of 10 degrees / minute, and kept at 500 degrees for 30 minutes, and then the temperature is normally raised to the sintering temperature. The initial firing temperature is 820-850°C, the initial rolling amount is 20% of the total thickness of the copper layer, the re-firing temperature is 870-900°C, and the re-rolling amount is 10% of the total thickness of the copper layer.

[0020] Furthermore, the method for preparing the sliding bearing blank further comprises step S7: adding lubricating oil to the sliding bearing blank formed after sintering.

[0021] Compared with the prior art, the sliding bearing blank provided by the present invention first provides a mixture of copper-tin-nickel alloy powder and copper powder during preparation, wherein the content of the copper powder in the mixture is 5-20%, and the particle size of the copper powder is 0.013 mm-0.045 mm. After the mixture is laid on a substrate, and a vibration machine is used to vibrate at a frequency of 20-50 Hz, all or part of the copper powder will fall on the surface of the substrate through the pores of the copper-tin-nickel alloy powder, thereby forming the unsintered sliding bearing blank. The unsintered sliding bearing blank includes a substrate, a copper powder layer laid on the substrate, and a copper-tin-nickel alloy powder layer located on the copper powder layer. After the unsintered sliding bearing blank is sintered, the copper powder layer will be sintered on the substrate to form a structure similar to a copper-plated layer, and the copper-tin-nickel alloy powder layer will be sintered on the copper layer to form a copper-tin-nickel alloy layer. Due to the presence of the copper layer, and the copper powder is non-spherical, the contact points with the substrate are more than those of spherical copper powder, thereby increasing the contact area between the copper powder and the substrate, forming a dense copper layer, and improving the bonding strength between the copper powder and the substrate. On the other hand, for the same reason, the contact area between the non-spherical copper powder and the spherical or ellipsoidal copper-tin-nickel alloy powder is larger, so that the sintering bonding strength between the copper layer and the copper-tin-nickel alloy layer is also better, thereby improving the bonding strength of the entire sliding bearing blank, especially for substrates with poor sintering composite performance, in the subsequent preparation process of the sliding bearing, whether it is turning or milling, bending or stretching, it will not crack or shift, thereby improving the product quality and service life of the sliding bearing. Since not all irregular copper powders will fall along the pores of the copper-tin-nickel alloy powder to reach the surface of the substrate, the copper powder remaining in the copper-tin-nickel alloy powder will reduce the overall porosity of the copper-tin-nickel alloy material, so a small amount of micro wax powder is added. At the same time, due to the presence of the micro wax powder, many pores will be formed in the copper plating layer and the copper-tin-nickel alloy layer after sintering, thereby maintaining the overall porosity of the copper-tin alloy material, ensuring the oil content of the sliding bearing, and ensuring the self-lubricating performance of the sliding bearing. Combining the above advantages, the sliding bearing blank has better bonding strength and can be used in more severe use environments, such as reciprocating, rotating, swinging, impact and other working conditions. At the same time, due to the use of a vibration machine, the powder can be spread once, which is conducive to realizing assembly line production. Therefore, the process method is efficient and convenient for realizing mass production and meeting the conditions for assembly line production. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 A schematic structural diagram of an unsintered blank of a sliding bearing provided by the present invention.

[0023] Figure 2 The present invention provides a flow chart of a method for preparing a sliding bearing blank.

[0024] Figure 3 for Figure 2 A schematic structural diagram of a sliding bearing blank prepared by the method for preparing a sliding bearing blank.

[0025] Figure 4 This is the microscopic morphology analysis of Comparative Example 1 provided by the present invention.

[0026] Figure 5 for Figure 2 Micromorphology analysis of the bearing shell of Example 2 prepared from the sliding bearing blank.

[0027] Figure 6 for Figure 2 Microstructure analysis of the bearing bush of Example 4 prepared from the sliding bearing blank DETAILED DESCRIPTION

[0028] The specific embodiments of the present invention are further described in detail below. It should be understood that the description of the embodiments of the present invention herein is not intended to limit the protection scope of the present invention.

[0029] like Figure 1 As shown, the present invention provides a schematic structural diagram of an unsintered blank of a sliding bearing. The unsintered blank of the sliding bearing comprises a substrate 10, a copper powder layer 20 laid on the substrate 10, and a copper-tin-nickel alloy powder layer 30 located on the copper powder layer 20. The content of the copper powder in the mixture of the copper powder used to form the copper powder layer and the copper-tin-nickel alloy powder used to form the copper-tin-nickel alloy powder layer is 5-20%, the content of the micro-wax powder is 0.1-0.5%, and the rest is copper-tin-nickel alloy powder. The particle size of the copper-tin-nickel alloy powder is 0.05mm-0.10mm and its shape is a round sphere or an elliptical sphere. The particle size of the copper powder is 0.013mm-0.045mm and its shape is non-spherical. The particle size of the micro-wax powder is less than 0.02mm, and the micro-wax powder is sandwiched between the copper powder and the copper-tin-nickel alloy powder.

[0030] The substrate 10 is a copper plate, a steel plate, a carbon steel plate, a stainless steel plate, or an aluminum plate. In this embodiment, the substrate 10 is a medium carbon steel plate, and its thickness can be determined according to actual needs.

[0031] The copper powder layer 20 is formed by laying copper powder. The copper powder is pure copper powder or copper alloy powder, and the copper alloy powder is one of brass, red copper, bronze, and white copper. The particle size of the copper powder is 0.013 mm to 0.045 mm and its shape is non-spherical. The particle size of the copper powder must be between 0.013 mm and 0.045 mm, so that the copper powder and the copper-tin-nickel alloy powder can be separated during preparation. Of course, it is not good to be too small, because if the particle size is too small, the copper powder will be completely separated from the copper-tin-nickel alloy powder, resulting in a decrease in porosity. If the particle size is too large, the copper powder will be built between the particles of the copper-tin-nickel alloy powder, making it difficult to separate. Of course, the particle size of the copper powder is also related to the particle size of the copper-tin-nickel alloy powder. However, for sliding bearings, the particle size of the copper-tin-nickel alloy powder is subject to national standards, that is, it is certain. The shape of the copper powder is non-spherical or can be irregular. The purpose of using irregularly shaped copper powder is to increase the contact area, not only to increase the contact area or contact point between the copper powder and the substrate 10, but also to increase the contact area or contact point between the copper powder and the copper-tin-nickel alloy powder particles, so as to improve the bonding strength between the copper powder and the substrate 10 after sintering, and to improve the bonding strength between the copper powder and the copper-tin-nickel alloy powder. Therefore, the particle size of the copper powder should be related to its content. The larger the content, the smaller the particle size should be, and vice versa. In this embodiment, the content of the copper powder in the mixture composed of the copper powder used to form the copper powder layer 20 and the copper-tin-nickel alloy powder used to form the copper-tin-nickel alloy powder layer 30 is 5-20%, and the particle size of the copper powder is 0.013mm-0.045mm. Preferably, when the content of the copper powder in the mixture is 6-15%, the copper powder has a particle size of 0.015mm to 0.035mm. Specifically, the copper powder has a content of 13% and a particle size of 0.017 mm. The copper powder has a content of 10% and a particle size of 0.025 mm.

[0032] The copper-tin-nickel alloy powder layer 30 is made of copper-tin-nickel alloy powder. The copper-tin-nickel alloy powder is CuSn8Ni1, which is a prior art and a commonly used alloy powder for preparing sliding bearings, and will not be described in detail here. The particle size of the copper-tin-nickel alloy powder is 0.05 mm to 0.10 mm and its shape is a round sphere or an ellipsoidal sphere. Preferably, the particle size of the copper-tin-nickel alloy powder is 0.08 mm. The copper-tin-nickel alloy powder is a round sphere or an ellipsoidal sphere, which should be a prior art, that is, when the manufacturer ships the copper-tin-nickel alloy powder, the shape is a round sphere or an ellipsoidal sphere. It can be imagined that the shape of the copper powder should be customized for the customer according to the requirements of the present invention.

[0033] The micro wax powder can be made of spherical high-density polyethylene. The micro wax powder is mixed in the copper powder and the copper-tin-nickel alloy powder. The content of the micro wax powder is 0.1-0.5%, preferably, the content of the micro wax powder is 0.3%. The particle size of the micro wax powder is less than 0.02 mm. Since the micro wax powder itself has a certain viscosity, when the micro wax powder is evenly dispersed and mixed into the copper powder and the copper-tin-nickel alloy powder, it will adhere to the particles of the copper powder and the copper-tin-nickel alloy powder, so that the micro wax powder can be clamped between the copper powder and the copper-tin-nickel alloy powder. Of course, the method of dispersing and mixing the micro wax powder into the copper powder and the copper-tin-nickel alloy powder should be a prior art and will not be repeated here. By increasing the micro wax powder, the porosity of the sliding bearing can be appropriately increased after sintering, and the lubrication performance of the sliding bearing will not be reduced due to the addition of the copper powder.

[0034] like Figure 2 As shown, the present invention also provides a method for preparing a sliding bearing blank, which comprises the following steps:

[0035] S1: providing a mixture of copper-tin-nickel alloy powder, copper powder, and micro-wax powder, wherein the content of the copper powder in the mixture is 5-20%, the content of the micro-wax powder is 0.1-0.5%, and the rest is copper-tin-nickel alloy powder, the particle size of the copper-tin-nickel alloy powder is 0.05mm-0.10mm and the shape is round spherical or elliptical spherical, the particle size of the copper powder is 0.013mm-0.045mm and the shape is non-spherical, and the particle size of the micro-wax powder is less than 0.02mm;

[0036] S2: providing a substrate 10;

[0037] S3: stirring the mixture of the copper-tin-nickel alloy powder, copper powder and micro wax powder evenly and spreading it on the surface of the substrate 10;

[0038] S4: providing a vibration machine, and placing a substrate covered with the mixture of the copper-tin-nickel alloy powder, copper powder, and micro wax powder on the vibration machine;

[0039] S5: starting the vibration machine and controlling the frequency of the vibration machine to be 20-50 Hz, the vibration time is 30 seconds when the thickness of the mixture is less than or equal to 0.5 mm, the vibration time is 100 seconds when the layer thickness of the mixture is greater than 0.5 mm and less than or equal to 2.0 mm, and the vibration time is 150 seconds when the copper powder layer thickness is greater than 2.0 mm, so as to separate the copper powder and the copper-tin-nickel alloy powder into layers, and closing the vibration machine after separation;

[0040] S6: sintering the substrate on which the layered copper powder and copper-tin-nickel alloy powder are laid and rolling to prepare a high-stability sliding bearing blank;

[0041] S7: Add lubricating oil to the high-stability sliding bearing blank formed after sintering.

[0042] In step S4 , the vibration machine itself is a prior art, and has a stage, and the substrate 10 is placed on the stage.

[0043] In step S5, the vibration time required for different thicknesses is different because the thicker the thickness, the more powder is spread, and the thinner the thickness, the less powder is spread. The thicker the thickness, the longer it takes for the fine powder to penetrate into the surface of the substrate, so the vibration time will be different for different thicknesses. Of course, there is no need to make the vibration time particularly long to waste time and energy. Therefore, in an embodiment, when the thickness of the mixture is less than or equal to 0.5mm, the vibration time is 30 seconds, when the layer thickness of the mixture is greater than 0.5mm and less than or equal to 2.0mm, the vibration time is 100 seconds, and when the thickness of the copper powder layer is greater than 2.0mm, the vibration time is 150 seconds. In step S6, sintering should be performed in batches, the initial sintering temperature is 820-850℃, the initial rolling amount is 20% of the total thickness of the copper layer, the re-firing temperature is 870-900℃, and the re-rolling amount is 10% of the total thickness of the copper layer. The initial sintering temperature is 820-850°C, the initial rolling amount is 20% of the total thickness of the copper layer, the re-sintering temperature is 870-900°C, and the re-rolling amount is 10% of the total thickness of the copper layer.

[0044] like Figure 3 As shown, the blank of the sliding bearing prepared by the above preparation method includes a substrate 10, a steel sintered layer 40, and a copper-tin-nickel alloy sintered layer 50. The copper sintered layer 40 is a dense layer with a porosity of less than 0.1%. The copper-tin-nickel alloy sintered layer 50 has a porosity of 2-8%.

[0045] Through the above preparation method, sliding bearings of the same specifications were made with medium carbon steel as the substrate. The test materials were processed into strips of 30*7*5mm and tested with reference to the nonferrous metal industry standard of the People's Republic of China "YS-T485-2005". The specific results are shown in Table 1.

[0046] Table 1 Shear strength test data of comparative examples and specific embodiments

[0047]

[0048] As can be seen from Table 1, the sintering bonding strength between the white blank substrate and the copper-tin-nickel alloy powder is poor, only about 120MPa, which cannot meet the requirements of post-processing and actual working conditions, especially the working environment with impact conditions. However, after the white blank substrate is copper-plated, the sintering bonding strength between the copper-plated substrate and the copper-tin-nickel alloy powder is significantly improved, reaching 235MPa. After adding irregular copper powder in different proportions to the copper-tin-nickel alloy powder, the bonding strength between the white blank substrate and the copper-tin-nickel alloy powder is significantly improved, and is proportional to the proportion of copper powder added. When the proportion of copper powder added reaches 10%, the bonding strength between the white blank substrate and the copper-tin-nickel alloy powder is equivalent to the bonding strength between the copper-plated substrate and the copper-tin-nickel alloy powder. When the proportion of copper powder added is above 15%, the bonding strength between the white blank substrate and the copper-tin-nickel alloy powder reaches more than 250MPa, which can basically meet the working environment with impact conditions.

[0049] When the above bearing materials are made into bearing test sleeves of the same specifications, sapphire fatigue strength test is carried out. The test conditions are a speed of 3000 rpm, first no-load operation for 30 minutes, and then a load of 20Mpa every 15 minutes for bearing running-in until the load reaches 100Mpa or the test temperature exceeds 150 degrees. After the test is completed, the final load is recorded and the appearance of the bearing material is microscopically analyzed. The specific results are shown in Table 2 and Figure 4 , Figure 5 , Figure 6 .

[0050] Table 2 Test data of bearings corresponding to different comparative examples and embodiments

[0051] substrate Copper layer composition Final load Microscopic morphology Comparative Example 1 Copper plating Copper-tin-nickel alloy powder 70MPa Obvious cracks Example 2 White Billet Copper-tin-nickel alloy powder + 10% copper powder added 90MPa Micro cracks Example 4 White Billet Copper-tin-nickel alloy powder + 20% copper powder added 100MPa No cracks

[0052] From Table 2 above, it can be seen that the final load of Example 2 after adding 10% copper powder is 90MPa, which is significantly higher than the 70MPa of Comparative Example 1 without adding any copper powder; and the final load of Example 4 after adding 20% ​​copper powder successfully completed the final loading procedure of 100MPa. The microscopic morphology analysis of the surface of the tested sample shows that there are many obvious cracks on the surface of the test sample of Comparative Example 1, and the cracks have a certain depth, indicating that the fatigue strength limit of the copper layer of the test sample of Comparative Example 1 has been reached under the test conditions; there is only one smaller microcrack on the surface of the test sample of Example 2, and it exists on the surface of the material, indicating that the test conditions are close to the fatigue strength limit of the copper layer of the test sample of Example 2; there are basically no cracks or microcracks on the surface of the test sample of Example 4, indicating that the fatigue strength of the bearing material can fully meet the conditions of 100MPa.

[0053] During the above test on the modified bearing material, it was unexpectedly found that irregular pure copper powder was added to the spherical copper-tin-nickel alloy powder. After sintering and rolling and other processing techniques, the overall fatigue strength of the material was unexpectedly improved. When the pure copper powder addition amount reaches more than 10%, the overall fatigue strength of the material can be significantly improved.

[0054] Combining the analysis of the metal powder sintering principle and metallographic structure, it was found that after adding irregular fine pure copper powder, a part of the pure copper powder was vibrated along the pores to form a transition copper layer on the surface of the substrate, and the other part of the pure copper powder was filled in the pores formed by the accumulation of spherical copper-tin-nickel alloy powder, making the overall loose structure more compact, increasing the contact points between metal powders, thereby increasing the contact area between metal powders. Small-particle copper powder can connect large-particle copper powders and promote the formation of sintering necks during the sintering process. From the perspective of thermodynamics and kinetics, it promotes the process of mutual melting of large-particle copper-tin-nickel alloy powders, obtaining better sintering effects, thereby obtaining a more compact metallographic structure, and then improving the bonding strength inside the copper layer, which is ultimately manifested as an improvement in the fatigue strength of the bearing material.

[0055] Compared with the prior art, the sliding bearing blank provided by the present invention first provides a mixture of copper-tin-nickel alloy powder and copper powder during preparation, wherein the content of the copper powder in the mixture is 5-20%, and the particle size of the copper powder is 0.013 mm-0.045 mm. After the mixture is laid on a substrate 10, and a vibration machine is used to vibrate at a frequency of 20-50 Hz, all or part of the copper powder will pass through the pores of the copper-tin-nickel alloy powder and fall on the surface of the substrate 10, thereby forming the unsintered sliding bearing blank. The unsintered sliding bearing blank includes a substrate 10, a copper powder layer 20 laid on the substrate 10, and a copper-tin-nickel alloy powder layer located on the copper powder layer. After the unsintered sliding bearing blank is sintered, the copper powder layer will be sintered on the substrate to form a structure similar to a copper-plated layer, and the copper-tin-nickel alloy powder layer will be sintered on the copper layer to form a copper-tin-nickel alloy layer. Due to the presence of the copper layer, and the copper powder is non-spherical, the contact points with the substrate are more than those of spherical copper powder, thereby increasing the contact area between the copper powder and the substrate, forming a dense copper layer, and improving the bonding strength between the copper powder and the substrate. On the other hand, for the same reason, the contact area between the non-spherical copper powder and the spherical or ellipsoidal copper-tin-nickel alloy powder is larger, so that the sintering bonding strength between the copper layer and the copper-tin-nickel alloy layer is also better, thereby improving the bonding strength of the entire sliding bearing blank, especially for substrates with poor sintering composite performance, in the subsequent preparation process of the sliding bearing, whether it is turning or milling, bending or stretching, it will not crack or shift, thereby improving the product quality and service life of the sliding bearing. Since not all irregular copper powders will fall along the pores of the copper-tin-nickel alloy powder to reach the surface of the substrate, the copper powder remaining in the copper-tin-nickel alloy powder will reduce the overall porosity of the copper-tin-nickel alloy material, so a small amount of micro wax powder is added. At the same time, due to the presence of the micro wax powder, many pores will be formed in the copper plating layer and the copper-tin-nickel alloy layer after sintering, thereby maintaining the overall porosity of the copper-tin alloy material, ensuring the oil content of the sliding bearing, and ensuring the self-lubricating performance of the sliding bearing. Combining the above advantages, the sliding bearing blank has better bonding strength and can be used in more severe use environments, such as reciprocating, rotating, swinging, impact and other working conditions. At the same time, due to the use of a vibration machine, the powder can be spread once, which is conducive to realizing assembly line production. Therefore, the process method is efficient and convenient for realizing mass production and meeting the conditions for assembly line production.

[0056] The above are only preferred embodiments of the present invention and are not intended to limit the protection scope of the present invention. Any modification, equivalent substitution or improvement within the spirit of the present invention is included in the scope of the claims of the present invention.

Claims

1. A method for preparing a sliding bearing blank, comprising the following steps: S1: providing a mixture of copper-tin-nickel alloy powder, copper powder and micro-wax powder, wherein the content of the copper powder in the mixture is 5-20%, the content of the micro-wax powder is 0.1-0.5%, and the rest is copper-tin-nickel alloy powder, the particle size of the copper-tin-nickel alloy powder is 0.05mm-0.10mm and the shape is round spherical or elliptical spherical, the particle size of the copper powder is 0.013mm-0.045mm and the shape is non-spherical, and the particle size of the micro-wax powder is less than 0.02mm; S2: providing a substrate; S3: stirring the mixture of the copper-tin-nickel alloy powder, copper powder and micro wax powder evenly and spreading the mixture on the surface of the substrate; S4: providing a vibration machine, and placing a substrate covered with the mixture of the copper-tin-nickel alloy powder, copper powder and micro wax powder on the vibration machine; S5: starting the vibration machine and controlling the frequency of the vibration machine to be 20-50 Hz, the vibration time is 30 seconds when the thickness of the mixture is less than or equal to 0.5 mm, the vibration time is 100 seconds when the layer thickness of the mixture is greater than 0.5 mm and less than or equal to 2.0 mm, and the vibration time is 150 seconds when the copper powder layer thickness is greater than 2.0 mm to separate the copper powder and the copper-tin-nickel alloy powder into layers; S6: Sintering the substrate on which the layered copper powder and copper-tin-nickel alloy powder are laid and rolling to prepare the sliding bearing blank.

2. The method for preparing a sliding bearing blank according to claim 1, characterized in that: In step S6, during the initial firing, when the sintering temperature reaches 200 degrees, the heating rate is controlled, and the temperature is slowly raised to 500 degrees at a rate of 10 degrees / minute, and kept at 500 degrees for 30 minutes, and then the temperature is normally raised to the sintering temperature. The initial firing temperature is 820-850°C, the initial rolling amount is 20% of the total thickness of the copper layer, the re-firing temperature is 870-900°C, and the re-rolling amount is 10% of the total thickness of the copper layer.

3. The method for preparing a sliding bearing blank according to claim 1, characterized in that: The method for preparing the sliding bearing blank further comprises step S7: adding lubricating oil to the high-stability sliding bearing blank formed after sintering.

4. The method for preparing a sliding bearing blank according to claim 1, characterized in that: The substrate is medium carbon steel, high carbon steel, aluminum plate or stainless steel plate.

5. The method for preparing a sliding bearing blank according to claim 1, characterized in that: The content of the copper powder is 13%, and the particle size of the copper powder is 0.017 mm.

6. The method for preparing a sliding bearing blank according to claim 1, characterized in that: The content of the copper powder is 10%, and the particle size of the copper powder is 0.025 mm.

7. The method for preparing a sliding bearing blank according to claim 1, characterized in that: The copper powder has a particle size of 0.015 mm to 0.035 mm, and the content of the copper powder in the mixture is 6-15%.

8. The method for preparing a sliding bearing blank according to claim 1, characterized in that: The copper-tin-nickel alloy powder is CuSn8Ni1.

9. The method for preparing a sliding bearing blank according to claim 1, characterized in that: The copper powder is pure copper powder or copper alloy powder, and the copper alloy powder is one of brass, red copper, bronze and nickel silver.

10. The method for preparing a sliding bearing blank according to claim 1, characterized in that: In S5, after the copper powder and the copper-tin-nickel alloy powder are layered, an unsintered sliding bearing blank is formed. The unsintered sliding bearing blank includes the substrate, a copper powder layer laid on the substrate, and a copper-tin-nickel alloy powder layer located on the copper powder layer, and the micro wax powder is sandwiched between the copper powder and the copper-tin-nickel alloy powder.

Citation Information

Patent Citations

  • Slide bearing composite material

    CN102369366A

  • Novel sliding bearing sintering blank

    CN217095672U